The Transmission of Mental Health within Households: Does One Partner's Mental Health Influence the Other Partner's Life Satisfaction? - Silvia Mendolia; Paul McNamee; Oleg Yerokhin (Institute of Labor Economics (IZA), 2018)
This paper investigates the relationship between partner's mental health and individual life satisfaction, using a sample of married and cohabitating couples from the Household, Income and Labour Dynamics of Australia Survey (HILDA). We use panel data models with fixed effects to estimate the life satisfaction impact of several different measures of partner's mental health and to calculate the Compensating Income Variation (CIV) of them. To the best of our knowledge, this is the first paper to study the effect of partner's mental health on individual's wellbeing and to measure the impact of reduced life satisfaction in monetary terms. We also provide some new insights into adaptation and coping mechanisms. Accounting for measurement error and endogeneity of income, partners' mental health has a significant and sizeable association with individual well-being. The additional income needed to compensate someone living with a partner with a long term mental condition is substantial (over USD 60,000). Further, individuals do not show significant adaptation to partners' poor mental health conditions, and coping mechanisms show little influence on life satisfaction. The results have implications for policy-makers wishing to value the wider effects of policies that aim to impact on mental health and overall levels of well-being.
Keywords: I10; I12; 330; partner's health; compensating income variation; fixed effects